A multifactorial injury prevention intervention reduces injury incidence in Physical Education Teacher Education students. Issue 3 (2nd April 2016) - Goossens, L.; Cardon, G.; Witvrouw, E.; Steyaert, A.; De Clercq, D.
Abstract: Physical Education Teacher Education (PETE) students are at considerable risk for non-contact sports injuries of the lower extremities. Multifactorial injury prevention interventions including exercises have been successful in sports populations, but no such study has ever been performed in PETE students. This study investigated the efficacy of a multifactorial injury prevention intervention on injury incidence reduction in PETE students. PETE students in the intervention group ( n = 154) and in the control group ( n = 189) registered sports injuries prospectively. The intervention lasted one academic year and consisted of an injury awareness programme and preventive strategies, implemented by the PETE sports lecturers. Differences in injury incidence between the intervention and control group were tested by Poisson regression Wald tests. There was a trend towards significantly lower incidence rate (2.18 vs. 2.73; p = 0.061) in the intervention group compared with the control group. Students in the intervention group had significantly less acute, first-time and extracurricular injuries. The largest reduction was observed for injuries during unsupervised practice sessions. A multifactorial injury prevention intervention embedded into a regular PETE programme is a promising and feasible strategy to prevent injuries in PETE students. Further research is needed to investigate whether the results may be generalised to other PETE programmes.